MiR-128-3p Post-Transcriptionally Inhibits WISP1 to Suppress Apoptosis and Inflammation in Human Articular Chondrocytes via the PI3K/AKT/NF-κB Signaling Pathway - Shujun Chen (Cell Transplantation, 2020)
In osteoarthritis (OA), the synthesis and decomposition of the extracellular matrix (ECM) are imbalanced. High expression levels of Wnt1-inducible signaling pathway protein 1 (WISP1) promote the synthesis of matrix metalloproteinases and induce the degradation of cartilage, which aggravates the OA. The aim of this study was to explore the role of miR-128-3p in the development of OA. In the present study, the expression of WISP1 and miR-128-3p in osteoarthritic tissues and chondrocytes was detected using quantitative reverse transcription PCR (RT-qPCR) and Western blotting. Then we predicted that WISP1 might be a potential target gene of miR-128-3p by TargetScan and verified using luciferase reporter gene assay. The effect of miR-128-3p or WISP1 on chondrocytes was evaluated by cell proliferation assay, apoptosis, and caspase-3 activity assay. To further reveal the molecular mechanisms of miR-128-3p in osteoarthritic development, the degradation of chondrocyte matrix and production of proinflammatory cytokines in osteoarthritic chondrocyte model were detected by ELISA. To mimic the osteoarthritic microenvironment in vitro studies, chondrocytes were stimulated with interleukin (IL)-1β, and then we found that the expression of miR-128-3p was downregulated. Overexpression of WISP1 inhibited the proliferation of chondrocytes, which induced apoptosis, degradation of chondrocyte matrix, production of proinflammatory cytokines, and activated the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt)/nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway. Then, we identified that miR-128-3p was a negative regulator of WISP1 by directly targeting its 3′-untranslated region (UTR). Moreover, the PI3K allosteric activator 740 Y-P abolished the inhibition of miR-128-3p in apoptosis, degradation of chondrocyte matrix, and inflammation. Our results showed that miR-128-3p targets WISP1 to regulate chondrocyte proliferation, apoptosis, degradation of chondrocyte matrix, and production of proinflammatory cytokines via the PI3K/Akt/NF-κB pathway, which plays a suppressed role in OA.